An overview of gravitational waves : theory, sources and detection - Auger, G.; Plagnol, E. (World Scientific, 2017)
"This book describes detection techniques used to search and analyse gravitational waves (GW). It covers the whole domain of GW detection, starting from the theory and ending with the experimental techniques (both present and future) used to detect them. The theoretical sections of the book address the theory of GW in the general relativity followed by the theory of GW detection. The different sources of GW are described as well as the methods used to analyse them and to extract the physical parameters of the sources. With the recent announcement of gravitational wave detection and the first results from LISA Pathfinder, this book will allow non-specialists to understand the present status of the field and the future of gravitational wave detection"--